Dynamics of a High-Power AMB–Multirotor Drivetrain - Jastrzebski Rafal P.; Putkonen Atte; Zhuravlev Andrei; Choudhury Tuhin; Sikanen Eerik; Kurvinen Emil; Pyrhönen Juha (Institute of Electrical and Electronics Engineers, 2025)
Active magnetic bearings are commonly applied in high-speed rotors in the medium to high power range to replace rolling-element or oil-film bearings. They require less maintenance and provide a number of unique benefits owing to their contactless suspension and active control. A rotor construction with integrated compressors or turbines results in predictable and controllable rotor dynamics, where model-based controllers can be used. Model-based centralized controllers outperform decoupled transfer function controllers, but they require accurate plant models. For integrated impellers on a single rotor, the control models comprise a rigid rotor and the lowest frequency bending modes. The bending mode frequency and parameters related to node locations can be identified, yielding controllers tuned to the application. This work introduces drivetrain modeling and magnetic levitation control of a 2 MW rotor and an external load attached to the electric machine rotor with a radially stiff but flexural coupling. The model-based control is tested in an experimental setup, and the drivetrain frequency responses are compared with the modeled multirotor drivetrain dynamics.